Endoscopic lymph node dissection for thymic malignancies: lateral thoracic intercostal and subxiphoid approaches - Suda, Takashi (Mediastinum; Vol 3 (April 2019): Mediastinum, 2019)
The significance of lymph node dissection for thymic malignancies is currently unclear. Recently, endoscopic surgery has been indicated for the surgical treatment of thymic malignancies. We discussed the range of possible lymph node metastasis following surgery for thymic malignancies, depending on whether the lateral thoracic intercostal or the subxiphoid approach was used. While the video-assisted thoracoscopic surgery (VATS) lateral approach cannot be used for lymph nodes in the anterior region on the opposite side, it is simple enough to be used for deep-region lymph nodes. Taking an approach from the right facilitates paratracheal lymph node dissection. Taking an approach from the left may facilitate para-aortic and subaortic lymph node dissection. In addition, placing the patient in the lateral decubitus position also facilitates subcarinal lymph node dissection. The advantages of the subxiphoid approach are that a good field of vision of the cervical region can be obtained with a camera inserted from the midline of the body and the phrenic nerve on both sides can be confirmed. Accordingly, anterior lymph node dissection can be performed in a manner similar to median sternotomy. Deep-region lymph node dissection is more difficult via the subxiphoid approach than via the lateral thoracic intercostal approach. While paratracheal lymph nodes can be dissected to some extent, it is difficult to dissect subcarinal lymph nodes. If one prioritizes thorough anterior region lymph node dissection, either the subxiphoid or the bilateral lateral thoracic region approach needs to be taken. The subxiphoid approach offers the same view from the body midline as median sternotomy. Therefore, it is superior to the VATS lateral approach with regard to region lymph node dissection.